<span>A) Y= -5x+3
B) -x -7y = 13 substituting equation A) into B)
B) -x -7*(-5x +3) = 13
</span>
<span>B) -x +35x -21 = 13
B) 34x = 34
x = 1
</span>
<span>A) Y= -5*1 +3
A) Y= -2
</span>
One sixth of an hour is 10 minutes.
That means it costs 5,700 every 10 minutes.
Costs 5,700 = 10 minutes
Dive 10 on both sides.
Costs 570 = 1 minute
Lets convert the minute into seconds.
Costs 570 = 60 seconds
Divide both sides by 60.
Costs 9.5 cents = 1 second
Round it off since you can't pay 9.5 cents.
Costs 10 cents = 1 second
This means that every second they pay 10 cents for the hotel. :D
the answer is, c) distributive
Answer:
The 1st term is -67
Step-by-step explanation:
I. When Sn =
(
)
If Sn = 124, n = 8 and
= 98
124 = 8/2(a + 98)
124 = 4(a + 98)
124 = 4a + 392
124 - 392 = 4a
-268/4 = a
-67 = ![a_{1}](https://tex.z-dn.net/?f=a_%7B1%7D)
Hope that help :D
You have been reading your book for about 7 days
7(10) pages each day + 9 left
70+ 9 = 69